Legal Counseling on "Itsbat Marriage" to Increase Community Legal Awareness - Ya` Rakha Muyassar; Syarifah Arrabiyah; M Fahmi Hazdan (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Marriage registration is mandated by Law Number 1 of 1974 concerning Marriage (Marriage Law), as stated in the provisions of Article 2. Further explanations regarding Itsbat marriage (marriage ratification) are found in the provisions of Article 7 of the Compilation of Islamic Law (KHI). This legal counselling aims to raise legal awareness among the community about the importance of marriage registration and Itsbat marriage in the village of Punggur Besar, which has a significant impact, particularly on women and children. This is closely related to legal certainty and protection, both during and after marriage dissolution. The method used in this community service activity is Participatory Rural Appraisal (PRA). This method is based on the participation of the attendees, including village elements, policymakers, and the surrounding community. It is employed to evaluate the participation of village elements and the community in the assessment process of this activity. This method actively interacts directly with stakeholders to achieve the desired results. The education session took place on December 24, 2022, in Punggur Besar Village, Kubu Raya Regency, and was attended by village officials and residents. Instruments such as pre-tests were used to ask oral questions to assess the community's knowledge about marriage registration and Itsbat marriage. The education revealed that there are still marriages conducted without marriage registration. Based on the results of the education, it is evident that increasing knowledge about marriage registration and Itsbat marriage is crucial, as it significantly impacts both the level of legal awareness among the community and the certainty and legal protection for the parties involved.Top of Form